PEMBINAAN IKLIM KASIH SAYANG TERHADAP ANAK DALAM KELUARGA - Nurbayani, Nurbayani (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2019)
This paper intends to provide an overview of the importance of affection for children in the family. This writing is based on the needs of children in their childhood because they have not yet perfect knowledge and mental readiness to live together with adults. Therefore parents have the task of providing education that can accommodate their instinctive natural needs. Children are God's mandate that needs to be given education. The process of children's education starts from the mother’s womb until adulthood. Parents have the responsibility of educating children in the right way in accordance with Islamic teachings. The main obligation is to instill faith in a child's soul. Muslim families who are builded on the basis of faith have the following identities: first, the righteous beliefs and to Allah SWT. Second, worship (al-ibadah ash-shahihah) in accordance with the shari'ah of Allah and His Messenger. And third, applying moral values (al-Akhlaqul karimah) in the family through education in the household. To realize the responsibility of taking care of children need several strategies.